Case series of keloid wedge resection in the ear: a focus on aesthetic aspects - Sihyun Yoon; Seung Han Song; Youngwoong Choi (Archives of Aesthetic Plastic Surgery, 2022)
Keloid scars may cause a range of symptoms and aesthetic problems. The ear is one of the most frequent sites of keloids, and the earlobe and ear helix account for more than 80% of ear keloids. There are various surgical methods for removing keloids in the ear. Standard keloidectomy and core excision can be effective surgical methods compared to wedge resection since they preserve normal tissue surrounding the keloid. However, ears often show various types of asymmetry by default, which can be relatively difficult to detect, so wedge resection continues to be a useful surgical method for ear keloids. Here, we report four cases of keloids in the earlobe and ear helix that were successfully treated by wedge resection without a postoperative deformity or recurrence.